Decreased Frequency of Intestinal CD39+ γδ+ T Cells With Tissue-Resident Memory Phenotype in Inflammatory Bowel Disease - Libera, Jana; Wittner, Melanie; Kantowski, Marcus; Woost, Robin; Eberhard, Johanna M.; de Heer, Jocelyn; Reher, Dominik; Huber, Samuel; Haag, Friedrich; Schulze zur Wiesch, Julian (Frontiers in Immunology, 2020)
The ectoenzymes CD39 and CD73 play a major role in controlling tissue inflammation by regulating the balance between adenosine triphosphate (ATP) and adenosine. Still, little is known about the role of these two enzymes and ATP and its metabolites in the pathophysiology of inflammatory bowel disease (IBD). We isolated mononuclear cells of peripheral blood and lamina propria of the large intestine of patients diagnosed with IBD and from healthy volunteers. We then comprehensively analyzed the CD39 and CD73 expression patterns together with markers of activation (HLA-DR, CD38), differentiation (CCR7, CD45RA) and tissue-residency (CD69, CD103, CD49a) on CD4+, CD8+, ɣδ+ T cells and mucosa-associated invariant T cells (MAIT) using flow cytometry. CD39 expression levels of ɣδ+ and CD8+ T cells in lamina propria lymphocytes (LPL) were much higher compared to peripheral blood mononuclear cells (PBMC). Moreover, the frequency of CD39+ CD4+ and CD8+, but not ɣδ+, LPL positively correlated with T-cell activation. The frequency of CD39+ cells among tissue-resident memory LPL (Trm) was higher compared to non-Trm on all subsets, confirming that CD39 is a marker for the tissue-resident memory phenotype. ɣδ+ Trm also showed a distinct cytokine profile upon stimulation - the frequency of IFN-ɣ+ and IL-17A+ cells was significantly lower in ɣδ+ Trm compared to non-Trm. Interestingly, we observed a decreased frequency of CD39+ δ+ T cells in IBD patients compared to healthy controls (p=0,0049). Prospective studies need to elucidate the exact role of this novel CD39+ ɣδ+ T-cell population with tissue-resident memory phenotype and its possible contribution to the pathogenesis of IBD and other inflammatory disorders.